Personality disorders and violence: what is the link?. Issue 1 (December 2015) - Howard, Richard
Abstract Despite a well-documented association between personality disorders (PDs) and violence, the relationship between them is complicated by the high comorbidity of mental disorders, the heterogeneity of violence (particularly in regard to its motivation), and differing views regarding the way PDs are conceptualised and measured. In particular, it remains unclear whether there is a causal relationship between PDs and violence, and what the psychological mechanisms might be that mediate such a relationship. Here, a perspective on PD and violence is offered that views the relationship between them through the lenses of the Five Factor Model of personality and a quadripartite typology of violence. Evidence is reviewed suggesting that emotion dysregulation/impulsiveness, psychopathy, and delusional ideation conjointly contribute to the increased risk of violence shown by people with PD, and do so by contributing to a broad severity dimension of personality dysfunction. This view is consistent with the abandonment of personality disorder categories in the forthcoming eleventh edition of the International Classification of Diseases (ICD-11), where severity of personality disorder is defined in terms of the degree of harm to self and others.